Brokerage in urban networks on diversity and inclusion: The case of Rotterdam. (April 2023) - Schiller, M.; Awad, I.; Buijse, N.; Chantre, M.; Huang, Y.-C.; Jonitz, E.; van den Brink, L.; van Dordrecht, L.
Abstract: Urban governance research posits a trend towards more cooperation between state and non-state actors. We also know that civil society organizations working on common issues often reinforce each other to secure a stronger voice. However, little research so far brings together urban governance and civil society coordination. This is particularly interesting for the action and policy field of diversity and inclusion, given its constant flux, multi-dimensionality, and political salience, as well as the many competing actors and agendas. Based on an in-depth case study of the city of Rotterdam, this article investigates the relations among organizations that focus on the interests of migrants and other marginalized residents and between these organizations and the municipality. We use qualitative and quantitative Social Network Analysis and draw on 27 semi-structured qualitative interviews as well as 25 network maps carried out with and drawn by representatives of civil society organizations. Our findings show a stratified governance network of actors working on diversity and inclusion in Rotterdam, where only a few large organizations serve as brokers, facilitating exchange but sometimes also reinforcing existing power relations. These findings underscore the importance of critically reviewing the collaborative character of urban governance in practice. Highlights: Local governance involves power relations. Civil society organizations that act as brokers can facilitate exchange, but also can reinforce hierarchy. Social Network Analysis allows to capture networks of urban actors working on diversity and inclusion. Rotterdam's model of governing has led to instability for civil society organizations working on inclusion and diversity.